Conflict Of Regional Expansion In Indonesia - Suraji, Ahmad Bakri Putra ,Muhamad Ali Embi (International Journal of Advanced Science and Technology, 2020)
The context of regional expansion which is synergized with decentralization and regional autonomy is thewill of reform and regional demands, but in its implementation it is not proportional to the expectationsthat are the goals of the pemekaran policy. According to Tryatmoko (2010) the issue of local governabilityis not only marked by weakness or expansion of the results of regional expansion, but also the weakness ofthe ability of the community to support local political and economic development. Furthermore Tryatmoko(in Ratnawai as Isabella Jenin argues) that the issue of the effectiveness of government policy in governingconcerns efficiency and legitimacy. While the issue of consent from the governed includes the involvementof the public in decision making and oversight of the netting of government. In this case, the division ofregions needs to receive attention and supervision, and it will gradually carry out and carry out theevaluation in stages.